Asaka Construction Company: Cadangan membina banglo 2 tingkat Lot 59, Jalan Kurt Donald, Cahaya Masai, 81750 Masai, Johor / Mohd Afif Aiman Jamil ... [et al.] - Jamil, Mohd Afif Aiman; Kamaruddin, Muhamad Nor Asyraf; Yahya, Muhammad Sahidi; Kamaruzaman, Mohd Kamarul; Hassan, Nurhazira (2016)
The ultimate goal of this report is to assist students in the reinforced concrete and steel structures design and guide them to design structurally safe buildings. This program also provide as much basic information to users. RC structural design does not restrict user to use just one answer but provides many possibility of structural member design for a set of building condition. Thus each calculation was divided into several steps. Also, Graphic User Interface (GUI) was used to provide visual output instead of numerical one and follow same colour coding pattern in the design. All modules use blue to depict good design, red for bad design, green for compression value, and purple for tension value. Several improvements can be made to reinforced concrete and steel structural design, most important of which could be the inclusion of 3D graphical output. Most architecture students are familiar with 3D-computer graphics such as AutoCAD. If reinforced concrete design used the 3D graphic output, it will be really helpful to students to understand the structure and connection between structural members.